Occurrence of parasites at the fish breeding stations in peninsular Malaysia and their control. - M., Shariff (1983)
In order to enhance the development of aquaculture in Malaysia, the Government has 8 freshwater fish breeding stations to provide fish seed for farmers. In the past, these breeding stations have had occasional problems of fish mortalities. A study was conducted to investigate the causes of such fish mortalities at the breeding stations. The results revealed that the common causes in the order of frequency of occurrence were; Ichthyophehirius multifilHs, Lernaea cyprinacea, monogenetic trematodes (Gyrodactylus and DactylOgyrus), Trichodina, fungal infection and OOdinium. During the period 1981 - 1982, an average number of three outbreaks occurred in the fish breeding stations per year. On the occurrence of such outbreaks the average mortalities incurred were associated With Trichodina (60%), monogenetic trematodes (58.5%), Lernaea clPrinaceae (55.5%), fungal infections (50.9%). Ichtbyopthirius multifiliis (35%) and Oodinium (20%). Low temperatures was found to be an additional contribu.ting factor for the mortalities at one of the highlands statibns where the temperature ranged between 17 - 24°C and the ~rtality rate was as high as 40% in one year i.e. 1982. In the' other stations with higher temperatures (26 -32°C) the average mortality was only 10%. Myxobolull sp. was found on common carp. This is the first record of the occurrence of Myxobolus sp. in cultured fish in Malaysia. Argulus'japonicus was also recorded at the breeding stations. The possible sources of ectoparasites in the breeding stations is discussed and the prevention and control of such ectoparasites is also presented.